AKTIVITAS SGOT, SGPT DI PENDERITA LUKA BAKAR SEDANG DAN BERAT - Hidayah, Sri Nurul; ., Mutmainnah; Samad, H. Ibrahim Abd. (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Burn injury is a kind of trauma with the high mortality and morbidity rate that needs special treatment since the very first phase up to the end. this study targeted medium to severe burns, limited to liver complications. the objective of this study is to calculate and observe the difference Sgot, SgPt activities in medium and severe burns. the Methods of this study was Cross Sectional, we conducted on 42 subjects with medium to severe burns, Hospitalised during the period of June 2005 to May 2007 at DR.Wahidin Sudirohusodo hospital of Makassar. the data were calculated and statistically analysed using the SPSS V.11.5. We obtained of 12 (28.6%) medium burn injuries and 30 (71.4%) severe burn injuries. In medium burn subjects the got showed normal activities in 6 subjects (50%) and high activities in 6 subjects (50%), the gPt showed normal activities in 8 subjects (66,7%) and high activities in 4 subjects (33.3%). In severe burn subjects the got showed normal activities in 6 subjects (20%) and high activities in 24 subjects (80%), the gPt showed normal activities in 13 subjects (43.3%) and high activities in 17 subjects (56.7%). there was no significant difference in the increasing activities of Sgot and SgPt in either medium or severe burns, where p > 0.05. Increased activities of SgPt and Sgot was higher in severe burns than in medium ones. It was also obtained that increasing Sgot activities was found more often than SgPt in patients with either medium or severe burns.